Irrigation scheduling, crop choices and impact of an irrigation technology upgrade on the Kansas High Plains Aquifer - Upendram, Sreedhar (Kansas State University, 2009)
The High Plains aquifer is a primary source of irrigation in western Kansas. Since World War II, producers increased irrigation and the irrigated acreage with the widespread adoption of newer irrigation technologies, causing a reduction in the saturated thickness of the High Plains aquifer. In an effort to conserve water and reduce further decline of the aquifer, the state of Kansas administered cost-share programs to producers who upgraded to an efficient irrigation system. But evidence suggests that the efforts to reduce water consumption have been undermined by producers, who under certain conditions have increased irrigation and irrigated acreage of high-valued and water-intensive crops. The state of Kansas is in a quandary to reduce water consumption and stabilize the saturated thickness of the aquifer while maintaining the economic viability of irrigated agriculture. A producer is faced with the choice of crop, irrigation timing and irrigation technology at the start of the season. This research identifies the conditions for risk-efficient crop choices and estimates the effect of an irrigation technology upgrade on the aquifer. Simulation models based on data from Tribune, Kansas were executed under various scenarios, varying by crop (corn or sorghum), irrigation system (conventional center-pivot or center-pivot with drop nozzles) and well capacity (190, 285 or 570 gallons per minute). Each well capacity was associated with a pre-season soil moisture level (0.40, 0.60 or 0.80 of field capacity). Each scenario was simulated over weather data observed during the 36-year period (1971-2006). Results indicate that producers with slower wells could maximize their net returns while conserving water by choosing less water-intensive crops like sorghum, while irrigating with a conventional center-pivot irrigation system. Producers with faster wells could maximize net returns by choosing water-intensive crops like corn and irrigate with the more efficient center-pivot with drop nozzle irrigation system. In order to reduce groundwater consumption and maintain the saturated thickness of the aquifer, water policies should internalize the interests of all stakeholders and be a combination of irrigation technology, economic factors, hydrological conditions, agronomic practices, conservation practices and local dynamics of the region.
Keywords: Irrigation scheduling; High Plains Aquifer; Irrigation technology upgrade; risk-efficient crop choices; center-pivot irrigation system; Economics, Agricultural (0503)